Pengaruh Inovasi Produk, Financial Technology (Fintech), dan Strategi Bisnis terhadap Kinerja UMKM di Kota Makassar - Nur Indah Cahyani; Ansyarif Khalid; Ismail Badollahi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The performance of Micro, Small, and Medium Enterprises (MSMEs) is increasingly influenced by their ability to innovate, adapt to digital financial services, and implement effective business strategies. Despite the growing adoption of digital technology among MSMEs, empirical evidence integrating product innovation, financial technology (fintech), and business strategy within a single analytical framework remains limited, particularly in the context of Makassar City. This research investigates the effects of product innovation, fintech utilization, and business strategy on MSME performance using a quantitative explanatory approach. Data were collected from 100 MSME owners selected from a population of 32,739 registered business units through a structured Likert-scale questionnaire distributed online. The data were analyzed using multiple linear regression with SPSS version 26 after passing validity, reliability, and classical assumption tests. The findings indicate that product innovation, fintech, and business strategy each exert a positive and significant influence on MSME performance. Fintech demonstrates the strongest contribution, followed by business strategy and product innovation. The coefficient of determination shows that the proposed model explains 39.4% of the variation in MSME performance. These findings highlight the importance of integrating continuous product development, digital financial services, and adaptive competitive strategies to strengthen business growth, operational efficiency, and sustainability. The study contributes to the literature by providing empirical evidence from a rapidly developing regional economy and offers practical implications for MSME development policies.